PERBANDINGAN USIA IBU PADA KEJADIAN PREEKLAMSIA DAN EKLAMSIA DI RSUP DR. M. DJAMIL PADANG TAHUN 2022 - Try Junira Putri; Vaulinne Basyir; Yulistini Yulistini; Bobby Indra Utama; Dian Pertiwi; Noverika Windasari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: One of the biggest contributors to Maternal Mortality Rate (MMR) in Indonesia is hypertension in pregnancy (preeclampsia and eclampsia). Apart from that, preeclampsia and eclampsia also have an effect on the health of the fetus which can ultimately cause fetal death. One of the risk factors for preeclampsia and eclampsia is maternal age Objective: This study aims to determine the comparison of maternal age in the incidence of preeclampsia and eclampsia at RSUP Dr. M. Djamil Padang in 2022 Methods: The research design used in this research is a cross-sectional study. The sampling technique in this study was total sampling, the population consisted of all patients diagnosed with preeclampsia and eclampsia at RSUP Dr. M. Djamil Padang in 2022, with total data including 94 out of 177 people. The secondary data used in this study was patients’ medical records that are presented tables. Data processing in this research uses the T-test Result: of this study obtained data on 72 preeclampsia patients and 22 eclampsia patients. The distribution of the highest maternal age group in preeclampsia patients and eclampsia patients is 20-35 years. The mean age of preeclampsia patients was 31.44 years, while the mean age of eclampsia patients was 28.41 years. The p value in this study was 0.025 (p<0.05) Conclusion: in this study there was a significant difference between maternal age in the incidence of preeclampsia and eclampsia at RSUP Dr. M. Djamil Padang in 2022